Perubahan Penggunaan Lahan dan Pendapatan Masyarakat di Kecamatan Sumberjaya, Kabupaten Lampung Barat, Propinsi Lampung - Bambang Soeharto; Cecep Kusmana; Dudung Darusman; Didik Suharjito (Institut Pertanian Bogor, 2011)
Total income in Sumberjaya sub-district, West Lampung District, Lampung Province is affected by land use system composition. Amount of 150 respondents in three villages Tribudi Sukur, Sukajaya and Simpangsari had been interviewed to get the information of household income. Simulation based on land use change scenarios (scenario 1: 13°/o monoculture coffee; scenario 2: 61°/o multistrata coffee; scenario 3: 23°/o forest; scenario 4: 30% forest and scenario 5: 84% forest) were done to predict total community income in different type composition. Highest total community income occurred when 61 °/o of total area covered by agroforestry base on coffee, but the lowest income occurred when 84°/o of area covered by forest. Converting 4°/o of existing shrub and 9°/o of monoculture coffee to agroforestry base on coffee will increase 12.1°/o total income. In opposite,reforestation all Sumberjaya sub-district areas, except paddy field, horticulture land and settlement will decrease 92°/o of total income.